Nishida Kitaro’s Expressive Activity in Katana Sword Making as a Way to Achieve Pure Experience - Mardohar Batu Bornok Simanjuntak (Dekonstruksi, 2023)
Western craft and craftmanship have long been taken as complementary or even supplementary – in contrast with high art and artistic explorations. This pejorative approach is quite common from western industrial perspective. An artisan’s work is then taken less seriously than an artist’s oeuvre d’art. Contrary to this, Asian countries have long recognised the mastery of these master craftsmen and gave no different treatment to artists and artisans. This paper examines the concept of expressive activity from Japanese philosopher Nishida Kitaro in his essay “Expressive Activity” written in 1925. In this Nishida proposes that the fulfilment of a state of mind that he called pure experience can only be achieved through an action that is independent from external urges. The author then pursued this line of thought by taking Nishida’s idea to see how this kind of acting – as Nishida addresses it – is present in the ancient craft of katana (Japanese Sword) making performed by veteran swordsmiths. By analysing Nishida’s texts including An Inquiry into the Good and Ontology of Production, the author explains that the old wisdom of “giving life to the steel” can be justified by taking Nishida’s pure experience as the telos of an artisan’s expressive activity.